2013
DOI: 10.1007/s13277-013-1271-4
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against p16 protein-derived peptides may be a potential biomarker for non-small cell lung cancer

Abstract: Overexpression of tumor-associated antigens (TAAs) has been reported in many types of cancer and may trigger secretion of their autoantibodies. The present work was thus designed to test whether circulating antibody to p16 protein-derived antigens was altered in lung cancer. Two hundred seventy-one patients with non-small cell lung cancer (NSCLC) and 226 control subjects matched in age, gender, and smoking history were recruited in this study. The levels of circulating anti-p16 IgA and IgG antibodies were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
2
17
2
Order By: Relevance
“…Other TAAbs were excluded from the review because relevant data were available from fewer than 3 articles . Five of the included studies examined only small-cell lung cancer (SCLC) [45,50,52,58,67], and eight included only non-small cell lung cancer (NSCLC) [28,47,54,55,57,59,64,109]. A total of 50 articles were based on serum specimens, while the remaining 3 were based on plasma samples.…”
Section: Basic Information About the Included Studiesmentioning
confidence: 99%
“…Other TAAbs were excluded from the review because relevant data were available from fewer than 3 articles . Five of the included studies examined only small-cell lung cancer (SCLC) [45,50,52,58,67], and eight included only non-small cell lung cancer (NSCLC) [28,47,54,55,57,59,64,109]. A total of 50 articles were based on serum specimens, while the remaining 3 were based on plasma samples.…”
Section: Basic Information About the Included Studiesmentioning
confidence: 99%
“…The autoantibody specific for FOXP3 protein was measured by a relative ELISA approach as described in our recent publication [11][12][13][14][15][16]. To reduce the interference from a non-specific signal produced by passive absorption of various IgG antibodies in plasma to the surface of a 96-well microplate, a specific binding index (SBI) was used to express the levels of circulating autoantibody against FOXP3.…”
Section: Autoantibody Testingmentioning
confidence: 99%
“…For example, the level of ABCC3 autoantibodies in patients with lung and esophageal cancers [11,12], p16 autoantibodies in patients with esophageal cancer and non-small-cell lung cancer [13,14], ANXA1 autoantibodies in patients with lung cancer [15] and FOXP3 autoantibodies in patients with esophageal cancer [16] are significantly higher than in healthy subjects. However, only a few studies on autoantibodies in patients with cervical cancer have been reported.…”
mentioning
confidence: 99%
“…For example, Looi et al developed an in-house enzyme-linked immunoassay (ELISA) using recombinant p16 protein as antigens to detect anti-p16 IgG levels in the plasma of cancer patients (18) and they observed a significant increase in the prevalence of IgG antibodies to the p16 protein in breast cancer. Based on our recent studies, the application of linear peptides as antigens may be more sensitive for ELISA in studying circulating antibodies against certain TAAs (20)(21)(22). Linear peptide antigens may be completely exposed and specifically bound to the corresponding antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…ELISA was developed in-house using a linear peptide antigen, as described in our recent publications, in order to detect circulating IgG to linear peptide antigens derived from the p16 protein (21,22). Briefly, the linear peptide antigen was synthesized by solid-phase chemistry, with a purity of >95%; a synthetic peptide (H-VFQKLKDLKDYGGVSLPEWVCIAFHTSG-OH) derived from a goat α-lactalbumin protein (accession 1FKV_A) was used as the control antigen.…”
Section: Introductionmentioning
confidence: 99%